Inequalities for Unified Integral Operators via Strongly α,h‐m-Convexity - Zhongyi Zhang; Ghulam Farid; Kahkashan Mahreen (Journal of Function Spaces)
In this paper, we give a generalized definition namely strongly α,h‐m-convex function that unifies many known definitions. By applying this new definition, we present inequalities for unified integral operators which have connection with many of the well-known results for different kinds of convex functions. Moreover, this paper at once provides refinements and generalizations of a lot of fractional integral inequalities which are identified in remarks.